1956
DOI: 10.2134/agronj1956.00021962004800050004x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilizer for Corn Production on an Irrigated Chestnut Soil1

Abstract: SYNOPSISStudies of irrigated corn on old rotation plots on very fine sandy loam had the. following general results: In year of N fertilizer application, increased yields were influenced by season and soil productivity as well as by time and rate of application. Time of application had little influence on yield on -lo.w productivity soil. Marked yield increases from residual N were also influenced by the above factors. Fertilizer N was more efficient during year of application when applied before plowing, at pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1958
1958
1989
1989

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…ies as either percentage of applied N recovered in the harvested portion, generally the grain, or as grain yield increase due to applied N. Other work in Nebraska (Pumphrey and Harris, 1956;Bigeriego et al, 1979), Kentucky (Miller et al,197 5), Ontario (Stevenson and Baldwin, 1969), and Minnesota (Nelson and Mac-Gregor, 1973;Moncrief et al, 1984) has shown no difference in grain yield between planting time and sidedress applications. Excessive delays or unusually dry conditions have reduced yields from late application (Jung et a1., 1972;Lewis et a1., 1983).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…ies as either percentage of applied N recovered in the harvested portion, generally the grain, or as grain yield increase due to applied N. Other work in Nebraska (Pumphrey and Harris, 1956;Bigeriego et al, 1979), Kentucky (Miller et al,197 5), Ontario (Stevenson and Baldwin, 1969), and Minnesota (Nelson and Mac-Gregor, 1973;Moncrief et al, 1984) has shown no difference in grain yield between planting time and sidedress applications. Excessive delays or unusually dry conditions have reduced yields from late application (Jung et a1., 1972;Lewis et a1., 1983).…”
mentioning
confidence: 98%
“…;elle et al, 1981 ). Grain yields the following year were shown to be higher in response to greater amounts of residual N (Pumphrey and Harris, 1956;Olson et al, 1964;Herron et al, 1971;Rehm and Weise, 1975). Residual N potentially available for the following year's crop is also susceptible to loss by leaching or denitrification (Olson, 1979).…”
mentioning
confidence: 99%
“…Most studies of N uptake patterns in maize have shown maximum accumulation rates occur near silking (Jones and Huston, 1914;Sayre, 1948;Jordan eta!., 1950;Hay eta!., 1953;Hanway, 1962; Mengel and Barber, 1974;Bigeriego et a!., 1979). Nitrogen application, when delayed too long, decreases yield and fertilizer N recovery (Pumphrey and Harris, 1956;IAEA, 1970;Jung eta!., 1972).…”
mentioning
confidence: 99%
“…No phosphorus deficiencies existed on the sites of the first two seedings. Where Tripp soil has been heavily cropped, nitrogen has proved to be the major limiting plant nutrient ( 14,15). The nitrogen fertility status of the soil on which the first planting was made was much higher than that of the third planting because better nitrogen management practices had been used.…”
Section: Methodsmentioning
confidence: 99%